Safety, immunogenicity and efficacy after switching from reference infliximab to biosimilar SB2 compared with continuing reference infliximab and SB2 in patients with rheumatoid arthritis: results of a randomised, double-blind, phase III transition study. Issue 2 (17th October 2017) - Smolen, Josef S; Choe, Jung-Yoon; Prodanovic, Nenad; Niebrzydowski, Jaroslaw; Staykov, Ivan; Dokoupilova, Eva; Baranauskaite, Asta; Yatsyshyn, Roman; Mekic, Mevludin; Porawska, Wieslawa; Ciferska, Hana; Jedrychowicz-Rosiak, Krystyna; et al.
Abstract : Objectives: Efficacy, safety and immunogenicity results from the phase III study of SB2, a biosimilar of reference infliximab (INF), were previously reported through 54 weeks. This transition period compared results in patients with rheumatoid arthritis (RA) who switched from INF to SB2 with those in patients who maintained treatment with INF or SB2. Methods: Patients with moderate to severe RA despite methotrexate treatment were randomised (1:1) to receive SB2 or INF at weeks 0, 2 and 6 and every 8 weeks thereafter until week 46. At week 54, patients previously receiving INF were rerandomised (1:1) to switch to SB2 (INF/SB2 (n=94)) or to continue on INF (INF/INF (n=101)) up to week 70. Patients previously receiving SB2 continued on SB2 (SB2/SB2 (n=201)) up to week 70. Efficacy, safety and immunogenicity were assessed up to week 78. Results: Efficacy was sustained and comparable across treatment groups. American College of Rheumatology (ACR) 20 responses between weeks 54 and 78 ranged from 63.5% to 72.3% with INF/SB2, 66.3%%–69.4% with INF/INF and 65.6%–68.3% with SB2/SB2. Treatment-emergent adverse events during this time occurred in 36.2%, 35.6% and 40.3%, respectively, and infusion-related reactions in 3.2%, 2.0% and 3.5%. Among patients who were negative for antidrug antibodies (ADA) up to week 54, newly developed ADAs were reported in 14.6%, 14.9% and 14.1% of the INF/SB2, INF/INF and SB2/SB2 groups, respectively. Conclusions: The efficacy, safety and immunogenicity profiles remained comparable among the INF/SB2, INF/INF and SB2/SB2 groups up to week 78, with no treatment-emergent issues or clinically relevant immunogenicity after switching from INF to SB2. Trial registration number: NCT01936181; EudraCT number: 2012-005733-37.